2022
DOI: 10.1016/j.pmedr.2021.101683
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of myocardial infarction: Do illness perceptions predict preferences for health check results

Abstract: Illness perceptions are associated with attitudes towards preventive behaviors and are therefore crucial to consider in the context of prevention of cardiovascular diseases. We investigated illness perceptions of the public about myocardial infarction, and whether they predict public preferences for health check test results. A randomly selected sample (N = 423) of the Swedish public aged 40–70 completed an online-survey. It included the brief illness perception questionnaire, items assessing sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that personal stress perception may also be one of the important factors affecting health [34]. A study that assessed levels of stress perception and perceptions of whether stress was harmful to health in 28,753 participants showed that stress increased mortality only in those who self-assessed risk harmful to health [35].…”
Section: Chronic Stressmentioning
confidence: 99%
“…It is worth mentioning that personal stress perception may also be one of the important factors affecting health [34]. A study that assessed levels of stress perception and perceptions of whether stress was harmful to health in 28,753 participants showed that stress increased mortality only in those who self-assessed risk harmful to health [35].…”
Section: Chronic Stressmentioning
confidence: 99%
“…This assessment is needed to initiate the actions required to address the health of populations while utilizing the preventive or curative healthcare services suitable for each particular population. 2 Furthermore, perception of illness seriousness can be a factor that influences adherence to preventive 3 and healthcare-seeking 4 , 5 behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…14 By offering educational resources, workshops, and interactive sessions, a deeper understanding can be fostered, ensuring that patients and families are well-informed about the condition. 15,16 Aligning with the study's emphasis on tackling knowledge gaps, it is imperative for healthcare practitioners to craft evidence-based educational interventions that specifically target areas of misunderstanding. 17,18 The research findings underscore the significant psychological impact of psoriasis on both patients and their family members.…”
mentioning
confidence: 99%